2003
DOI: 10.1046/j.1460-9592.2003.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

The Defibrillation Efficacy of High Frequency Alternating Current Sinusoidal Waveforms in Guinea Pigs

Abstract: There have been few basic studies of alternating current (AC) defibrillation, despite growing interest in the ability of AC to terminate or alter ongoing fibrillation. Based on fibrillation threshold testing, it has been suggested that cardiac tissue is most sensitive to long duration, low strength AC stimulation at around 50 Hz. This has not been directly tested for defibrillation. Two subcutaneous electrodes were placed 40 mm apart on opposing aspects of the guinea pig thorax. Seven seconds were allowed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…AC has been used in intact guinea pig hearts, demonstrating a frequency-dependent increase in fibrillation induction threshold (19). The defibrillation efficacy in vivo in guinea pig hearts has been evaluated at AC frequencies up to 1 kHz but with a maximum duration of 32 cycles (20). Successful termination of VF in vivo required at least 80 cycles (400-ms duration at 200 Hz) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…AC has been used in intact guinea pig hearts, demonstrating a frequency-dependent increase in fibrillation induction threshold (19). The defibrillation efficacy in vivo in guinea pig hearts has been evaluated at AC frequencies up to 1 kHz but with a maximum duration of 32 cycles (20). Successful termination of VF in vivo required at least 80 cycles (400-ms duration at 200 Hz) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Weirich et al [39] applied alternating-current (AC) defibrillation waveforms with frequencies of 30-1000 Hz on guinea pig hearts and demonstrated that the fibrillation threshold increased when high frequencies were applied. One study demonstrated that 200 Hz had a higher defibrillation success rate than 1000 Hz did; however, the study had limited sampling frequencies [40]. High-frequency AC stimulation (1000-2000 Hz) can also inhibit cardiac excitation and generate reversible conduction blocks in cardiomyocytes [41].…”
Section: Plos Onementioning
confidence: 99%